Intellectual Grid Modulation and Monitoring - et. al., A. B. Abubakirov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article design of communicational devices and approbation of Intellectual Grid technologies are considered. As well the characteristics of the functional properties of Intellectual Grid technology are presented. Model of the electrical enginering system in complex program MATLAB (Simulink) are developed.